Pendampingan Pesantren Kilat Pada Santri Tarbiyah Putra Pondok Pesantren Al Urwatul Wutsqo Jombang - Sunardi Sunardi; Moh. Kholik; Senang Senang (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
Express Islamic Boarding School is an intensive and effective method of religious education for students, increasing their faith and Islamic knowledge. This research aims to provide assistance to the Kilat Santri Tarbiyah Putra Islamic Boarding School, with a focus on developing the quality of teaching and learning as well as managing the activities of the Lightning Islamic Boarding School. The research was carried out through a participatory approach involving Islamic boarding school administrators, teachers, and students. Assistance steps include needs mapping, preparation of teaching programs, teacher training, and regular evaluation. The results of this assistance show significant improvements in several aspects, including: The results of this assistance show significant improvements in several aspects, including increasing understanding of religious knowledge, worship, and the character of students. This research makes a positive contribution to improving the quality of religious education in the Islamic boarding school environment, as well as providing a basis for further development in efforts to support character and Islamic education for Santri